مساجد مصر الأثرية في أدب الرحلات الأردي: دراسة وصفية نقدية: رحلة سلمي أعوان "مصر ميرا خراب مصر حلمي" نموذجا - عبدالرحيم، عبدالرحيم عبدالغني محمد Abdulrahim, Abdulrahim Abdulghani Mohammed (جامعة الأزهر - كلية الدراسات الإنسانية, 2019)
يعمد البحث إلى دراسة رحلة (سلمى أعوان) إلى مصر؛ تلك الرحلة التي قدمت فيها تصورا خاصا عن بلدنا الحبيب مصر ومساجدها الأثرية، وما حباها الله به من تراث إسلامي عظيم، فضلا عن تعرض الكاتبة لعناصر الثقافة المصرية من عادات وتقاليد ومأكل وملبس، ولا يخفي ما في ذلك من أهمية للتعرف على رؤى الكاتبة وخلفياتها الفكرية عن ثقافتنا ومجتمعنا.
The study aims to study the journey of Salma Awan to Egypt; the journey in which she presented a special vision of our beloved country Egypt and its ancient mosques, and the great Islamic heritage that Allah distinguished it with, In addition, the writer exposes to the elements of Egyptian culture such as customs, traditions, food and clothing, which is important to know the Writer's views and intellectual backgrounds about our culture and society.
Keywords: الأثار -- آدب الرحلات الأردي -- مصر -- أعوان، سلمي